Juvenile hemochromatosis associated with B-thalassemia treated by phlebotomy and recombinant human erythropoietin - M De Gobbi; P Pasquero; F Brunello; P Paccotti; U Mazza; C Camaschella (Haematologica, 2000)
Juvenile hemochromatosis is a rare genetic disorder that causes iron overload. Clinical complications, which include liver cirrhosis, heart failure, hypogonadotropic hypogonadism and diabetes, appear earlier and are more severe than in HFE-related hemochromatosis. This disorder, therefore, requires an aggressive therapeutic approach to achieve iron depletion. We report here the case of a young Italian female with juvenile hemochromatosis who was unable to tolerate frequent phlebotomy because of coexistent ss-thalassemia trait. The patient was successfully iron-depleted by combining phlebotomy with recombinant human erythropoietin.